“Being a Person of Color in This Institution Is Exhausting”: Defining and Optimizing the Learning Climate to Support Diversity, Equity, and Inclusion at the University of Washington School of Public Health - Gwayi-Chore, Marie-Claire; Del Villar, Erika Lorenzana; Fraire, Lucia Chavez; Waters, Chloe; Andrasik, Michele P.; Pfeiffer, James; Slyker, Jennifer; Mello, Susan P.; Barnabas, Ruanne; Moise, Elba; Heffron, Renee (Frontiers in Public Health, 2021)
Learning climate greatly affects student achievement. This qualitative study aimed to understand community definitions of climate; share lived experiences of students, faculty, and staff; and define priority areas of improvement in the University of Washington School of Public Health (UWSPH). Between March-May 2019, 17 focus group discussions were conducted – stratified by role and self-identified race/ethnicity, gender and sexual orientation – among 28 faculty/staff and 36 students. Topics included: assessing the current climate, recounting experiences related to roles and identities, and recommending improvements. Transcripts were coded using deductive and inductive approaches. Race/ethnicity, gender, and sexual orientation appeared to affect perceptions of the climate, with nearly all respondents from underrepresented or minoritized groups recounting negative experiences related to their identity. Persons of color, women, and other respondents who identified as lesbian, gay, bisexual, transgender, queer/questioning, intersex, and asexual (LGBTQIA) frequently perceived the climate as “uncomfortable.” Most felt that UWSPH operates within a structural hierarchy that perpetuates white, male, and/or class privilege and “protects those in power” while leaving underrepresented or minoritized groups feeling like “the way to move up…is to conform” in order to not be seen as “someone pushing against the system.” Improvement priorities included: increasing community responsiveness to diversity, equity, and inclusion; intentionally diversifying faculty/staff and student populations; designing inclusive curricula; and supporting underrepresented or minoritized groups academically, professionally, and psychologically.